1988
DOI: 10.1111/j.1438-8677.1988.tb02137.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of macrofungi in two moist heathlands in Drenthe, The Netherlands

Abstract: In two plots, domin~ted by Erica tetralix and Molinia caerulea, respectively, carpophores ofmacrofungi were counted during 7 successive years with fortnightly intervals. The changes in the number of species, number of carpophores, carpophore productivity and productivity of dominant species are described and discussed. In addition, the periodicity of some species is treated. It appears that quantitative and qualitative changes in the two stands do not parallel each other. The changes are mainly interpreted as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 5 publications
0
39
0
1
Order By: Relevance
“…Studies based on macrofungal fruiting bodies have shown that even in areas that have been repeatedly sampled for many years, new species can be found (e.g., Arnolds, 1988;Perini et al, 1989;Tofts andOrton, 1998, Straatsma et al, 2001). Additionally, more taxonomic expertise is required for classical methods than for molecular methods, as all of the species must be identified based on morphological characters.…”
Section: Disadvantages Of Classical Methodsmentioning
confidence: 99%
“…Studies based on macrofungal fruiting bodies have shown that even in areas that have been repeatedly sampled for many years, new species can be found (e.g., Arnolds, 1988;Perini et al, 1989;Tofts andOrton, 1998, Straatsma et al, 2001). Additionally, more taxonomic expertise is required for classical methods than for molecular methods, as all of the species must be identified based on morphological characters.…”
Section: Disadvantages Of Classical Methodsmentioning
confidence: 99%
“…Arachniotus, Coprinus) II. Ectocoprophilous fungi Spores cannot germinate after passing the alimentary tracts of animals (probably Ascozonus) Arnolds (1981) distinguishes the proper (obligate) coprophilous fungi growing exclusively on dung e.g. Sacco bolus glaber, Anellaria semiovata, Strophana semiglobata, Psilocybe coprophila, and subcoprophilous fungi (facultative coprophytes) growing also on fertile habitats, e.g.…”
Section: Germination Conditions and Relations Between Coprophilous Fumentioning
confidence: 99%
“…Lisiewska 1974). Fungal communities on special substrates are regarded and classificated as autonomic mycocoenoses (Pirk and Tuxen 1949, Ebert 1958, Kreisel 1957, 1961, Kreisel and Muller 1987, Jahn 1966, 1976, Runge 1980 and others), or they are regarded as mycosocieties, whereas the term mycocoenosis is reserved to the complete assemblage of fungi growing within a certain biocoenosis (Barkman 1973, 1976a, Arnolds 1981.…”
mentioning
confidence: 99%
“…Among different natural environments, also considering their relationships between climate and vegetation (Blasi et al 1999), forests host the highest richness of macrofungi (i.e. fungi producing sporomata larger than 1 mm; Arnolds 1981). In the last century, their growth conditions were dramatically influenced by human activities.…”
Section: Introductionmentioning
confidence: 99%